2019
DOI: 10.5004/dwt.2019.24351
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced adsorption and desorption of phosphate on poly(acrylic acid-co-N-[3-(dimethylamino)propyl]acrylamide) hydrogels in aqueous solutions

Abstract: We explore the feasibility of using thermosensitive hydrogels based on copolymers of acrylic acid (AAC) and N-[3-(dimethylamino)propyl] acrylamide (DMAPAA) [P(AAC-co-DMAPAA)] for adsorption and desorption of phosphate in aqueous solutions by a temperature swing. The hydrogels were protonated when they swelled in acidic solution at room temperature, exhibiting good adsorption capacity of phosphate. The phosphate ions were desorbed at high temperature due to the ionic repulsion of carboxyl groups caused by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The value of pH pzc is the point where the curve of ΔpH (=pH f − pH i ) versus pH i crosses the line equal to zero by the pH drift method. 12,56,57 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Materials and Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of pH pzc is the point where the curve of ΔpH (=pH f − pH i ) versus pH i crosses the line equal to zero by the pH drift method. 12,56,57 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Materials and Experimental Sectionmentioning
confidence: 99%
“…XPS (250XI, Thermo ESCALAB) analyses of samples before and after adsorption were carried out by using an Al Kα ( h ν = 1486.6 eV, 150 W) X-ray radiation with a pass energy of 30 eV, and all the binding energies were calibrated against the C 1s peak at 284.8 eV. , The point of zero charge (pH pzc ) for samples was determined by measuring initial pH (pH i ) and final pH (pH f ) of the solution. The value of pH pzc is the point where the curve of ΔpH (=pH f – pH i ) versus pH i crosses the line equal to zero by the pH drift method. ,, …”
Section: Materials and Experimental Sectionmentioning
confidence: 99%
“…This indicates that the adsorption rate depends on the adsorption capacity and not on the concentration of adsorbates as defined by the chemical sorption, or chemisorption phenomenon. [54,55]…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…Therefore, the results clearly showed that the pseudo‐second order model was more suitable to describe the adsorption kinetic processes of different resins for Hg (II). This indicates that the adsorption rate depends on the adsorption capacity and not on the concentration of adsorbates as defined by the chemical sorption, or chemisorption phenomenon [54,55] …”
Section: Sorption Experimentsmentioning
confidence: 99%
“…The phosphate ions were subsequently desorbed at temperature above LCST due to the ionic repulsion of the carboxyl groups caused by the dissociation of hydrogen bonding. [183] Apart from regeneration of sorption sites, recovery or separation of the sorbents from the treated water is sometimes necessary, especially when the sorbents are formulated in micron-sized particles. Besides conventional sedimentation, hydrogel sorbents can be separated from water by various means such as magnetic induction, [52,133] or solar-triggered thermally induced dewatering.…”
Section: Novel Sorbent Regeneration Approachesmentioning
confidence: 99%